2004
DOI: 10.1002/elps.200406051
|View full text |Cite
|
Sign up to set email alerts
|

Complexation between low‐molecular‐weight cationic ligands and negatively charged polymers as studied by capillary electrophoresis frontal analysis

Abstract: The potential of using capillary electrophoresis frontal analysis for the study of low-molecular-weight ligand-polyelectrolyte interactions was assessed. The interaction of the ligands 1-propylpyridinium bromide, 2-propylisochinolinium bromide, and paraquat with the polymer dextran sulfate was investigated as a function of polymer concentration and ionic strength of the buffer solution. Linear binding isotherms were obtained and association constants were determined. The complex formation was independent of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 50 publications
3
21
0
Order By: Relevance
“…In line with previous studies [19], strong adsorption to the fused silica capillary wall was observed for methyl viologen (paraquat). Methyl viologen adsorbed onto PVA coated capillaries to a lesser extent indicating that the PVA coated capillary should be applied in the affinity studies encompassing methyl viologen.…”
Section: Methods Developmentsupporting
confidence: 92%
See 4 more Smart Citations
“…In line with previous studies [19], strong adsorption to the fused silica capillary wall was observed for methyl viologen (paraquat). Methyl viologen adsorbed onto PVA coated capillaries to a lesser extent indicating that the PVA coated capillary should be applied in the affinity studies encompassing methyl viologen.…”
Section: Methods Developmentsupporting
confidence: 92%
“…The construction of binding isotherms for determination of the apparent association constant K app has been described previously [19]. Briefly, the binding density, , was calculated from the measured free ligand concentration [L] free , the total ligand concentration [L] total, and the molar concentration of chondroitin sulfate disaccharide units, C CS :…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations